Dementia with Lewy bodies: Challenges in the diagnosis and management. (April 2019) - Chin, Kai Sin; Teodorczuk, Andrew; Watson, Rosie
Objective: Dementia with Lewy bodies is the second most common form of neurodegenerative dementia in older age yet is often under-recognised and misdiagnosed. This review aims to provide an overview of the clinical features of dementia with Lewy bodies, discussing the frequent challenges clinicians experience in diagnosing dementia with Lewy bodies, and outlines a practical approach to the clinical management, particularly in the Australian setting. Methods: This paper is a narrative review and a semi-structured database (PubMed and MEDLINE) search strategy was implemented. Articles were screened and clinically relevant studies were selected for inclusion. Results: Dementia with Lewy bodies is clinically characterised by complex visual hallucinations, spontaneous motor parkinsonism, prominent cognitive fluctuations and rapid eye movement sleep behaviour disorder. Neuropsychiatric features and autonomic dysfunction are also common. The new diagnostic criteria and specific diagnostic biomarkers help to improve detection rates and diagnostic accuracy, as well as guide appropriate management. Clinical management of dementia with Lewy bodies is challenging and requires an individualised multidisciplinary approach with specialist input. Conclusion: Dementia with Lewy bodies is a common form of dementia. It often presents as a diagnostic challenge to clinicians, particularly at early stages of disease, and in patients with mixed neuropathological changes, which occur in over 50% of people with dementia with Lewy bodies. Prompt diagnosis and comprehensive treatment strategies are important in improving patients' care.